2017
DOI: 10.1021/acs.cgd.6b01715
|View full text |Cite
|
Sign up to set email alerts
|

Strong-Acid-Templated Construction of a Metallosupramolecular Architecture: Reversible Ammonia Adsorption in Aqueous Media in a Single-Crystal-to-Single-Crystal Conversion Manner

Abstract: Creation of an acidic metallosupramolecular architecture templated by a strong Brønsted acid (HClO4) and its reversible adsorption/release of ammonia molecules in aqueous media are reported. The 1:1 reaction of a digold­(I) metalloligand, [Au2(trans-dppee)­(d-Hpen)2] ([H2 1]), with Ni­(OAc)2 yielded a {AuI 2NiII} n 1D coordination polymer ([2]). A similar reaction with Ni­(ClO4)2 produced a AuI 4NiII 2 hexanuclear complex, which co-crystallized with HClO4 to form a metallosupramolecular structure in [3]·2HClO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Thus, single crystals of 1 Na were soaked in 0.1 M aqueous ammonia overnight to confirm the presence of H 3 O + ions in 1 Na . 40 This treatment proceeded with retention of its crystallinity, and the elemental analytical data of the resulting crystals were in good agreement with the formula of ( (see Figure S10 in the Supporting Information). Thus, we concluded that 1 Na is a solid solution containing [Co III 2 (L Au ) 2 ] 2+ and [Ni II Co III (L Au ) 2 ] + in a 1:2 ratio, which was crystallized separately from [Ni II 2 (L Au ) 2 ].…”
Section: ■ Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, single crystals of 1 Na were soaked in 0.1 M aqueous ammonia overnight to confirm the presence of H 3 O + ions in 1 Na . 40 This treatment proceeded with retention of its crystallinity, and the elemental analytical data of the resulting crystals were in good agreement with the formula of ( (see Figure S10 in the Supporting Information). Thus, we concluded that 1 Na is a solid solution containing [Co III 2 (L Au ) 2 ] 2+ and [Ni II Co III (L Au ) 2 ] + in a 1:2 ratio, which was crystallized separately from [Ni II 2 (L Au ) 2 ].…”
Section: ■ Resultssupporting
confidence: 61%
“…While 8 nitrate anions are needed to balance the charge of the octahedron, a total of 12 nitrate anions exist in the crystal per the supramolecular octahedron; 1 is in the center of the octahedron, 1 is in the octahedral interstice, and 10 are in the hydrophilic tetrahedral interstice. We concluded that 4 water molecules located on 4 of the 8 trigonal faces of the supramolecular octahedron in 1 Na exist as H 3 O + to balance the charge, affording a chemical formula of (H 3 O) 2/3 [Au 4 Ni 2/3 Co 4/3 (dppe) 2 (D-pen) 4 ](NO 3 ) 2 for 1 Na (see Figures 2a and 2b + ions in a single-crystal-to-singlecrystal transformation process; 40 such an adsorption ability of ammonia molecules was not recognized for the CS-type structure of [Co III 2 (L Au ) 2 ](NO 3 ) 2 . Thus, single crystals of 1 Na were soaked in 0.1 M aqueous ammonia overnight to confirm the presence of H 3 O + ions in 1 Na .…”
Section: ■ Resultsmentioning
confidence: 99%
“…A similar reaction of [H 2 1 ] with Ni(OAc) 2 in a 1:1 ratio gave a blue solution, from which blue crystals of [ 3 Ni ] were isolated. The absorption spectrum of [ 3 Ni ] in methanol showed two bands in the visible to near‐IR region (593 nm and 1045 nm, Figure S9), which are characteristic of related gold(I)–nickel(II) multinuclear complexes with octahedral Ni II centers . X‐ray fluorescence spectroscopy indicated that [ 3 Ni ] contains Ni and Au atoms and the results of the elemental analysis were in agreement with the formula for a 1:1 adduct of [ 1 ] 2− and Ni 2+ .…”
Section: Methodsmentioning
confidence: 99%
“…[ 21,23 ] We have named this class of ionic solids the charge‐separation (CS) type, and several ionic solids with a similar CS‐type structure have also been synthesized by replacing dppe and Co III with other diphosphine ligands and metal ions, respectively. [ 33,34 ]…”
Section: Introductionmentioning
confidence: 99%
“…[21,23] We have named this class of ionic solids the charge-separation (CS) type, and several ionic solids with a similar CS-type structure have also been synthesized by replacing dppe and Co III with other diphosphine ligands and metal ions, respectively. [33,34] To expand the range of ionic solids having a CS-type structure, in this work, we employed D-H 4 ebp = N,N 0ethylenebis(D-penicillamine) as a thiol-containing amino acid, [35][36][37][38] instead of D-H 2 pen, for the construction of an analogous Au I 4 Co III 2 hexanuclear complex, expecting the formation of a different aggregated structure of counter anions due to the presence of an ethylene moiety that bridges two amine groups from two D-H 2 pen ligands. We found that the reaction of Na…”
Section: Introductionmentioning
confidence: 99%